Retrospective analysis of the application of the Braden Q scale in pediatric intensive care (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: to characterize the profile of patients who developed pressure injuries and to analyze the retrospective scores obtained in the application of the Braden Q Scale in pediatric intensive care. Method: retrospective cohort study with analysis of secondary data from 34 electronic medical records of patients admitted to pediatric intensive care. Results: from the analysis of the scores obtained with the application of the Braden Q Scale, six records of pressure injuries were identified; the average age was 8.1 years; 66.6% were male; average of 41 days of hospitalization; main diagnoses are related to diseases of the respiratory, cardiac and neurological systems; all used invasive mechanical ventilation support and had a fasting prescription and use of a nasogastric tube. Conclusion: the clinical profile is correlated with the male gender, the higher frequency of respiratory diseases requiring mechanical ventilation, the use of vasoactive, vasopressor and sedative drugs, and the tube as a route of dietary administration. All of them had high risk scores for developing pressure injuries.